The coffee shop experience and its associations with social capital and quality of life. (2018) - Menon, Rohit; Crawford, Pat; Lee, Eunsil; Kotval-K, Zeenat
A 'first place' is the home, while a 'second place' is the work setting. A 'third place' refers to places where people choose to linger. All three are keys to building social capital and improving quality of life. This study explored coffee shops in Greater Lansing, Michigan as a third place and its associations with social capital and quality of life. Survey participants (n = 196) rated factors that defined their social capital, their quality of life, and the importance of different elements within the coffee shop. Dimension reduction and multiple linear regressions were used to find significant relationships among the coffee shops to quality of life and to social capital. The quality of the intangible coffee shop characteristics significantly correlate with higher levels of quality of life and social capital. It is vital for business owners to celebrate the spirit of the place to improve the patrons' happiness in the third place.